HUBUNGAN ANTARA KEMAMPUAN MENGAJAR GURU DENGAN PRESTASI BELAJAR SISWA PADA MATA PELAJARAN AKIDAH AHKLAK DI MTs AL-FALAH RUPAT KABUPATEN BENGKALIS - Praziyanti, Fiza; Ritonga, Supardi (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
One component of the school that is very important for achieving success in learning is the teacher. The teacher's teaching ability has a relationship and influence on learning achievement and student success rates in the teaching and learning process. This study aims to determine the relationship between teacher teaching ability (independent variable) and student learning achievement (dependent variable) in moral creed subjects at MTs Al-Falah Rupat. The research was conducted at Madrasah Tsanawiyah Al-Falah Parit Kebumen, Rapat District, Bengkalis Regency from April to April June 2023. This type of research is quantitative research through a descriptive approach. The number of samples in the study was 49 students and one teacher. The data used are primary data and secondary data, where primary data is collected by questionnaires (questionnaires), interviews, documentation, while secondary data is collected from books or journals. In measuring the results of the questionnaire, researchers used the Likert Scale with answers.ie strongly agree (SS), agree (S), hesitate (RG), disagree (TS), strongly disagree (STS). The collected data was then analyzed using  SPSS 27 software with product moment correlation techniques. The results showed significant values of 0.001 < 0.005. This means that the significance value is smaller than 0.005, so there is a significant relationship between the teacher's teaching ability and student learning achievement. The pearson correlation value shows 0.513 which lies between 0.40 to 0.599. Thus it can be interpreted that between the two variables there is a moderate or sufficient correlation relationship